THE MAIN CAUSE OF HIV/AIDS INFECTION DISEASE - Fauzaania, Aannisah; Hasyim, Hamzah; Wulandari, Atik; Sumarni, Deasy; Fitrianto, Aidil; Anggriani, Bayu; meliyani, ani; Taher, Ahmad (LPPM Universitas Prima Nusantara Bukittinggi, 2021)
Â Background: The emergence of Human Immunodeficiency Virus (HIV) has delivered large fitness demanding situations to youngsters and young people round the sector manifesting as biological, psychological, and social problems. This then have become a worldwide project which isn't always simplest depending on the fitness quarter, however additionally the complete authorities quarter in widespread due to the effect of HIV sickness which has the capacity to assault all groups.Purpose: behavior a literature overview on HIV/AIDS. This literature overview will describe the primary reasons of HIV primarily based totally on a few dependable references.Method: the use of a literature overview with the database used is Pubmed, a literature seek method with the keywords